The Effects of Biochar Incorporation on the CO2, N2O, and CH4 Emissions from the Soils of Stallholder Palm Oil Plantations, Jambi Province Indonesia - Damris Muhammad; Ngatijo Ngatijo; Ira Galih Prabasari; Bunga Mardhotillah (Journal of Applied Agricultural Science and Technology, 2023)
The domestic agricultural sector contributes 18% to the national greenhouse gas emissions (GHG); which is higher compared to its global counterpart. Biochar incorporation into the soils shows the potential to reduce soil GHG emissions. The objective of this study was to ascertain how biochar addition affects CO2, N2O and CH4 emissions from the soils of stallholder palm oil plants. Coffee hash was pyrolyzed at 5000C to prepare biochar, which was then ground to pass a 100-mesh sieve. Three plots (50m x 50 m) consisting of 27 subplots (1 m x 1 m) were used as the experimental design in the field. Biochar was incorporated into the soil subplots of 0, 10, and 20-ton biochar/ha. A static chamber was installed on the soil surface to collect gas generated from the soil on days 0, 5, 10, 20, 40, and 60. All gas collection was conducted at 30 min after the chamber lid installation. The soil CO2, N2O, and CH4 emissions of control soils ranged from 712 to 862, 7.28 to 9.46, and -0.0036 to 0.0014 kg/d/ha, respectively. The incorporation of 10 and 20-ton biochar per hectare decreased the emissions of CO2 and N2O up to 16.8% and 33.8%, respectively; whereas an uptake was observed for the CH4 gas. The CO2 and N2O emissions from the 10-ton/ha and 20-ton/ha biochar-incorporated soils differ significantly compared to the control soils, but the CH4 emissions do not. This result shows that biochar incorporation to the oil palm soils reduces the CO2 and N2O emissions, but not CH4 emissions.